A critical appraisal of phloem-mobile signals involved in tuber induction - Suárez-López, Paula (Frontiers in Plant Science, 2013)
The identification of FLOWERING LOCUS T (FT) and several FT homologs as phloem-mobile proteins that regulate flowering has sparked the search for additional homologs involved in the long-distance regulation of other developmental processes. Given that flowering and tuber induction share regulatory pathways, the quest for long-distance tuberization signals has been further stimulated. Several tuberization regulators have been proposed as mobile molecules, including the FT family protein StSP6A, the plant growth regulators gibberellins and the microRNA miR172. Although some of these hypotheses are attractive and plausible, evidence that these molecules are transmissible in potato has yet to be obtained. Two mRNAs encoding transcription factors, StBEL5 and POTH1, are mobile and correlate with tuber induction. However, evidence that StBEL5 or POTH1 are required for tuberization is not available yet. Therefore, there are several good candidates for long-distance molecules in the tuberization process. Further research should test their role as systemic tuberization signals.